Semen dysbiosis—just a male problem? - Morawiec, Emilia; Czerwiński, Michał; Czerwińska, Anna Bednarska-; Wiczkowski, Andrzej (Frontiers in Cellular and Infection Microbiology, 2022)
Seminal microflora is crucial to male fertility. Dysbiosis—disturbance of quantitative ratios of individual bacteria or appearance of pathogenic species—rarely results in symptomatic disease. Inflammation results in decreased sperm production, lower motility, or morphological changes, and in the long term, can cause ejaculatory duct obstruction, leading to infertility. Moreover, it may cause infection of the partner’s female genital tract. Dysbiosis in both partners results in fertility problems, disorders in embryo implantation, or miscarriages. In addition, chronic inflammation of the male genitourinary system may accelerate the appearance of antisperm antibodies. A comprehensive examination of seminal microflora can clarify the causes of infertility or prevent pathological conditions that affect seminal parameters. Seminal microflora as a direct impact on fertility problems as well as a decrease in the effectiveness of assisted reproduction methods, insemination, or in vitro procedures.